The THE IMPORTANCE OF STUDENT-CENTERED LEARNING IN TODAY’S 5.0 EDUCATION SYSTEM - Nahdawati Nahdawati; Rahmatul Ummu Arifin (Scolae: Journal of Pedagogy, 2025)
In the era of Education 5.0, the learning process is no longer focused solely on knowledge transfer but also on developing students' critical thinking, creativity, collaboration, communication, and problemsolving skills. This study discusses the importance of Student-Centered Learning (SCL) as an instructional approach that places students at the center of the learning process. Through SCL, students actively participate in constructing knowledge, engaging in discussions, solving real-world problems, and reflecting on their learning experiences. This approach encourages learner autonomy, increases motivation, and supports the development of essential 21st-century competencies required in modern society. Furthermore, Student-Centered Learning aligns with the goals of Education 5.0 by integrating technology, innovation, and human-centered values into educational practices. The findings indicate that SCL contributes significantly to improving student engagement, academic achievement, and lifelong learning skills. Therefore, implementing Student-Centered Learning is crucial for preparing students to face the challenges and opportunities of the rapidly changing global environment.